2021
DOI: 10.1088/1361-648x/ac1de1
|View full text |Cite
|
Sign up to set email alerts
|

Topological properties of bulk and bilayer 2M WS2: a first-principles study

Abstract: Recently discovered 2M phase of bulk WS 2 was observed to exhibit superconductivity with a critical temperature of 8.8 K, the highest reported among superconducting transition metal dichalcogenides. Also predicted to support protected surface states, it could be a potential topological superconductor. In the present study, we perform a detailed first-principles analysis of bulk and bilayer 2M WS 2 . We report a comprehensive investigation of the bulk phase, comparing structural and electronic properties obtain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…The S p xy orbitals give almost half of the total DOS, while approximately 20% comes from the W d zy /d zx orbitals. In accordance with previous studies,19,27 the inclusion of spin-orbit coupling (SOC) is found to have only a minor effect. In particular, there is a small (33 meV) increase in the size of the gap formed between the valence and conduction bands just below the Fermi level at the G point (see Fig.S2(a) in the ESI †47 ).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…The S p xy orbitals give almost half of the total DOS, while approximately 20% comes from the W d zy /d zx orbitals. In accordance with previous studies,19,27 the inclusion of spin-orbit coupling (SOC) is found to have only a minor effect. In particular, there is a small (33 meV) increase in the size of the gap formed between the valence and conduction bands just below the Fermi level at the G point (see Fig.S2(a) in the ESI †47 ).…”
supporting
confidence: 91%
“…5,18 The resulting compounds are both metallic, and 2M-WS 2 exhibits superconductivity with a critical temperature ( T c ) of 8.8 K, the highest T c among superconducting TMDs at ambient pressure. In addition to being superconducting, this phase has been predicted, 5,19 and later confirmed, 20 to display topologically protected surface states with a single Dirac cone at the Brillouin zone (BZ) center. On the other hand, in the sister compound 2M-WSe 2 , superconductivity only appears under pressure at 4.2 GPa, and the critical temperature reaches a maximum value of 7.3 K at 10.7 GPa.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, a uniaxial strain reduces the symmetry of TMDs and gives rise to enhanced BCD [8][9][10]. Similar enhancements are also observed for few-layer TMDs [4][5][6]11], where the lowering of symmetry is the result of the stacking of monolayers. It has further been observed that the electric field can efficiently tune the anomalous NHE in lowsymmetry TMDs [12].…”
Section: Introductionmentioning
confidence: 79%
“…Such a non-linear Hall effect can also be generated in systems preserving time reversal (TR) symmetry, in contrast to the linear Hall effect [34][35][36]. Diverse set of materials have been predicted to show finite BCD and the resulting second order Hall effect, including two-dimensional materials [37][38][39][40][41], and Dirac and Weyl semimetals [42][43][44][45][46], strained bilayer and monolayer graphene [47] and Rashba systems [48]. Significant advances have also been made in the experimental detection of such Hall signals in several material platforms, starting with few-layer WTe 2 [49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%